Uréia como fonte alternativa de nitrogênio na micropropagação de abacaxizeiro cv. Pérola - Moreira, Maria Aparecida (2007)
The partial or total substitution viability of the ammonium nitrate for urea, as source of nitrogen in the culture medium for the in vitro culture of pineapple cv. Pérola was studied. Plants originating from fruit crown buds with fresh weight matter around 80 mg was inoculated on MS medium (liquid and solid) with substitution of 100, 80, 60, 40, 20 and 0% of the ammonium nitrate for urea. These treatments were arranged in a completely randomized design, with four replications and three plants/replications. After 60 days, the possibility of 40% ammonium nitrate for urea partial substitution was observed for the analyzed variables. In addition, better plant development in solid culture medium was observed as well.